Analysis of mangrove vegetation diversity in Pematang Kuala Village, Teluk Mengkudu Sub-district, Serdang Bedagai Regency, North Sumatra - Sitanggang, Miduk; Salomo Bobby Fernando Sihombing; Poppy Lumban Gaol; Rahmawaty; Seca Gandaseca; Mohd Hasmadi Ismail (Global Forest Journal, 2025)
Mangrove ecosystems are important in ecological, economic, and social aspects,especially for coastal communities. However, damage to mangrove ecosystemsdue to land-use changes for purposes such as settlements and fish ponds canthreaten their sustainability. This study aims to analyze the potential of themangrove ecosystem, apply the kao-kao model in silvofishery pond management,and analyze the potential of mangroves in increasing the income of the communityin Pematang Kuala Village, Teluk Mengkudu Sub-district, Serdang BedagaiDistrict, North Sumatra Province. The methods used include field surveys forvegetation analysis and interviews with Kelompok Usaha Bersama (KUB)Nelayan Sepakat members. Vegetation analysis was conducted in three zones:utilization zone I, II, and the protection zone. Each zone consisted of 5 plots,totaling 15 plots. Interviews were conducted with 27 respondents. The studyresults showed that the mangrove ecosystem in Pematang Kuala Village isdominated by Avicennia marina and Rhizophora mangle, with an important valueindex of 300 in both utilization and protection zones. In the protection zone, theShannon-Wiener diversity index was 0.95, indicating a low level of diversity.Based on the kao-kao system model, it was observed that the productivity of fishponds and fishermen's catch increased. Community income has significantlyincreased over the last five years, with an average net income of IDR 19,550,000every six months. The presence of mangroves also provides indirect benefits as acoastal protector from abrasion, with an estimated economic value of IDR247,950,000 per year.